Health, trust, or "just understood": explicit and implicit condom decision-making processes among black, white, and interracial same-sex male couples. - Campbell, Chadwick K; Gómez, Anu Manchikanti; Dworkin, Shari; Wilson, Patrick A; Grisham, Kirk K; McReynolds, Jaih; Vielehr, Peter; Hoff, Colleen (Archives of sexual behavior, 2014)
Among gay and bisexual men, primary partners are a leading source of HIV infection. Trust, intimacy, and advancements in HIV treatment may impact same-sex male (SSM) couples' decisions to engage in unprotected anal intercourse (UAI). This qualitative study explored how Black, White and interracial couples discussed, and made decisions regarding condoms. Qualitative interviews were conducted with 48 SSM couples in the New York and San Francisco metropolitan areas. Stratified purposive sampling was used to include Black (n = 16), White (n = 17), and interracial (Black-White) (n = 15) couples. Twenty-six couples were concordant HIV-negative and 22 were HIV-discordant. Interviews were recorded, transcribed, coded, and analyzed using a grounded theory approach. Some couples described explicit processes, which involved active discussion, while others described implicit processes, where condom-use decisions occurred without any explicit discussion. These processes also differed by race and HIV status. Black couples tended to report condom-use as "just understood." White, HIV-discordant couples decided not to use condoms, with some identifying the HIV-positive partner's suppressed viral load and high CD4 count as deciding factors. After an unplanned episode of UAI, White, HIV-negative couples tended to discontinue condom use while Black HIV-negative couples decided to revert to using condoms. HIV prevention efforts focused on same-sex, male couples must consider the explicit/implicit nature of condom decision-making processes. Understanding differences in these processes and considering relationship dynamics, across race and HIV status, can promote the development of innovative couple-level, HIV prevention interventions.
Keywords: Adult; African Americans; Bisexuality; Condoms; Decision Making; European Continental Ancestry Group; HIV Infections; HIV Seropositivity; Homosexuality, Male; Humans; Male; New York; Safe Sex; San Francisco; Sexual Behavior; Sexual Partners; Trust